Determinants of mental health in the workplace - Hosie, P.; Kingshott, Russel; Sharma, Piyush (2017)
Mental health problems in organizations impact on society. This chapter synthesizes the various strands of research and thinking about mental health in the workplace and identifies areas for testing constructs and their inter-relationships. It explores the magnitude and cost of mental health problems within society and the workplace; links between POS and mental health; the "happier-and-smarter" and "sadder-but-wiser" hypotheses; societal and institutional frameworks that impact on mental health; and finally the contribution, implications, and future research directions of mental health. It uses a simple methodology to identify the relevant extant literature suitable for analysis. A substantial number of high-quality reports into mental health were identified from countries in Europe, the United Kingdom, the United States, Australia, and Canada. The chapter examines websites of credible international organizations concerned with mental health, including the International Labour Organization, World Health Organization, and the US Department of Health and Human Services.